Understanding integrated working between arts and care settings: An analytical framework for planning and research. Issue 5 (9th December 2014) - Clark, Michael
Abstract : Purpose: – The purpose of this paper is to discuss integrated working between the arts and those in care settings. Identifying that the field is very broad, with diverse evidence and experience within it, the paper argues that there is a need to find ways in which to be clearer about the purpose of specific arts and care integrated projects. The paper draws on a case study project to develop some insights and a framework to help address this challenge. Design/methodology/approach: – The paper is a conceptual discussion and development drawing upon insights from relevant literature and a case study analysis of an integration project between a hospice service, an art gallery and an artist. Findings: – The integrated working case study project between the hospice, art gallery and artist highlights some points about a lack of conceptual frameworks to help locate the purpose of diverse arts and care projects. There is scope for much confusion about the nature and purpose of such integration projects without a clear framework for articulating the aims of individual integration endeavours and their place in relation to other arts and care work. This paper develops a framework and a clear understanding about the different kinds and goals of integrated working between arts and care settings to help with future practical and research projects. Research limitations/implications: – The paper reports a case study which highlights key themes from which generalisation to other services will require interpretation for particular contexts. Practical implications: – The ideas present a helpful approach to articulating the goals of individual projects and to better understand the place of projects in relation to other arts and care initiatives. Social implications: – There is much scope for better integrated working between arts and care settings to achieve better outcomes for users of care services, and the ideas presented here should help to better organise and evaluate such developments. Originality/value: – This is the first paper to set out the framework presented to help with better integrated working between arts and care settings.